FACE AND POLITENESS IN COMMUNICATION REVISITED - Quang, Nguyen (VNU Journal of Foreign Studies; Vol 35 No 2DO - 10.25073/2525-2445/vnufs.4345, 2019)
In this article, arguments of various conceptualisations of face and politeness are advanced and working definitions of them are offered. Hypotheses of ‘why politeness?’ and of positive-negative politeness preferences on the basis of communicative components (context of situation) and in correlation with other categorical dimensions (context of culture) are developed with confirmation that they simply serve as the starting point for empirical research to prove them right or wrong in particular contexts of situation and culture.